The Impact of the Covid-19 Pandemic on the MSME Sector in Tana Toraja - Dian Intan Tangkeallo; Dwibin Kannapadang (Universitas Kristen Indonesia Toraja, 2022)
The pandemic of COVID-19 has become a threat to multiple sectors, particularly the UMKM sector. Given that UMKM are the largest contributor to PDP and the sector that employs the most people, it is necessary to give the UMKM sector special attention. The purpose of the research was to assess the impact of the COVID-19 pandemic on the Tana Toraja UMKM sector. The research method employed is qualitative and descriptive, with data gathered via interviews with UMKM actors in the Makale central market. The results showed that not all UMKM were impacted by the COVID-19 pandemic. Some UMKM have survived due to their utilization of innovation and technology.